Respuesta :

Answer:

the desired equation is y = (1/6)x + 3/2.

Step-by-step explanation:

From the graph you can see immediately that the y-intercept is (0,3/2).

This is "b" in y = mx + b.

Focus on point (-3,1).  Substitute -3 for x in y = mx + 3/2 and then 1 for y:

1 = m(-3) + 3/2

Clear this result of fractions by mult. all three terms by 2:

2 = m(-6) + 3.  Solving for m, -6m = 2 - 3, or -6m = -1.  Then m = 1/6, and the

desired equation is y = (1/6)x + 3/2.


[tex]x - 6y = - 9[/tex]
3 - 6(2) = -9
3 - 12 = -9


If you plug the numbers in for x and y and end up with the correct solution then you'll know you've got the right equation.